Manajemen Mutu Guru (Implementasi Undang-undang, Peraturan dan Kebijakan) - Dwi Surya Atmaja (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
Through ASEAN Summits 1997 – 2007, leaders of ASEAN countries have achieved the agreement to establish AEC (Asean Economic Community) in the end of 2015, providing the ability to pursue the ASEAN vision 2025. By means of regional and then global free trade to come, the welfare of 660 millions people in ASEAN countries regarding those leaders. The question is what should be done by each member? In terms of free market, common quality standard comes in the first place. Consequently, terminologies such as accreditation and certification are among words which teachers pay a lot of attention. These two words are not only about quality standard they have to achieved but also result in their take home payment. This article aims to explain te rationale of “Quality Standard” as a must programme in free market era, regionally and globally.